Ureaplasma urealyticum and mycoplasma hominis in preterm labor - Passos, Mariana DL; Jayaram, Aswathi; Witkin, Steven S (Brazilian Journal of Sexually Transmitted Diseases, 2011)
Mycoplasma hominis and Ureaplasma urealyticum are considered genital mycoplasmas, because infection occurs through sexual contact. The presence of these bacteria has been associated with non gonococcal urethritis, cervicitis, vaginitis, pelvic inflammatory disease (PID) and pathology of pregnancy and newborns.Complications of genital mycoplasmas on the outcome of pregnancy include ectopic pregnancy, premature birth and preterm premature rupture of membranes (PPROM), chorioamnionitis, post partum endometritis, salpingitis, low weight and late abortion. This review article focuses on the importance of these microorganisms leading to preterm labor.